(untitled) (Journal of Namibian Studies : History Politics Culture, 2017)
The internment camp ‘Klein-Danzig’ in Windhoek was in existence during the first years of the Second World War between 1939 and 1941. Its overall capacity rose from 70 up to 200 men. Mainly based on a solid corpus of camp records which include a wide range of documents such as disciplinary files of internees, blue prints for the barracks or even dentist’s files, a detailed picture of the organization, social structure and all-day life in the Windhoek camp is given. The main focus of the article lies on the description of the internees’ disobedience and insubordination which finally led to the shut-down of the camp in 1941. A short summary of the history of the German speaking minority in South West Africa between the World Wars serves to put the internment camp into historical context.